Ab Initio and in-Crystal Geometry of trans-1,4-Dibromo1,4-dicarboxymethylcyclohexane - Echeverría, Gustavo Alberto (2000)
The structure of trans-1,4-dibromo-1,4-dicarboxymethylcyclohexane (I) has been determined by single crystal x-ray diffraction. The molecules, located on symmetry centers, are in the rigid chair conformation with the Br and COOCH3 axial and equatorial, respectively. The molecular geometry observed in the crystal is similar to that calculated for the isolated molecule using ab initio calculations performed at the HF/6-31(d) level. A peculiar arrangement of the carboxymethyl substituents, along with short contacts involving the Br atoms, seem to play a role in the stabilization of the crystalline structure.